Addressing climate risks mainstreaming climate change in development project planning and budgeting in Bangladesh - Perveen, MST Farida; Nahar, Nurun; Chowdhury, Farhat Jahan; Osti, Rabindra (Mandaluyong City, Metro Manila Asian Development Bank, 2023)
This brief shows how Bangladesh can improve development planning and boost resilience by comprehensively analyzing climate and disaster risk to better calculate possible economic losses and implement effective adaptation measures.
Keywords: Climate change -- Bangladesh; Climate finance -- Bangladesh; Promoting climate resilient development -- Bangladesh